An Analysis of Business Strategies and Managements Which Cause Company's Success or Challenges in the International Market: A Case Study in IKEA Company - Chen, Lang-Rong (2017)
There is a general agreement among researchers that the IKEA company which established in 1943 in Sweden has become one of the most famous international furniture retailer and opened massive stores all around the world. On account of that, many successful unique strategies and creative managements made by some famous companies which explored and studied by the researchers appear. However, there is some evidence to show that some successful companies such as IKEA may still have failures or face challenges during the steps of decision or the operation such as entering the USA market and quality issues about products, which need some effective actions to overcome and avoid them. This paper seeks to explore the operation of famous companies with the case study of IKEA company which create success or problems in the international level, and 3 main perspectives from the company are discussed: the company’s strategies, the organization’s managements and the international markets in the strategic management; and in the case, it also talk about company’s unique innovation, the success and the challenge. According with this, it argues, in general, that these useful business strategies and managements such as IKEA’s success has played an important role in the advancement of the company, it also suggests that some problems and challenges could not be avoided and still need to learn a lesson. It is recommended that further comprehensive studies should be conducted with the relation of the other business area of the company as well as to cover the topic from more various aspects and research fields.